SOME ASPECTS OF THE DEVELOPMENT OF MODERN STUDENT SPORTS IN THE REPUBLIC OF UZBEKISTAN - G. R. Muratova (Galaxy International Interdisciplinary Research Journal, 2023)
This article highlights the problems of the development of student sports in the Republic of Uzbekistan. Based on the analysis of the peculiarities of the organization of student sports abroad, attempts are made to find solutions to similar problems that relate to student sports in Uzbekistan.